Roadmap of Scanning Probe Microscopy - Morita, Seizo; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2007)
Scanning tunneling microscopy - with its applications that span not only atomic resolution but also scanning tunneling spectroscopy, atom/molecule manipulation and nanostructuring, and inelastic electron tunneling spectroscopy - has achieved remarkable progress and become the key technology for surface science. Besides, atomic force microscopy is also rapidly developing and achieving remarkable progress and accomplishments such as true atomic resolution, atom/molecule identification, manipulation and nanostructuring. This book that predicts the future development for all of scanning probe microscopy (SPM). Such forecasts may help to determine the course ultimately to be taken and to accelerate research and development on nanotechnology and nanoscience, as well as all SPM-related fields in future.
Science and Technology in the Twenty-First Century -- Scanning Tunneling Microscopy -- Atomic Force Microscopy -- Near-Field Scanning Optical Microscope -- Scanning Capacitance Microscope -- Electrostatic Force Microscopy -- Magnetic Force Microscope -- STM-Induced Photon Emission Spectroscopy -- Scanning Atom Probe -- Chemical Discrimination of Atoms and Molecules -- Manipulation of Atoms and Molecules -- Multiprobe SPM -- AFM Measurement in Liquid -- High-Speed SPM -- Scanning Nonlinear Dielectric Microscope -- SPM Coupled with External Fields -- Probe Technology -- Characterization of Semiconducting Materials -- Evaluation of SPM for LSI Devices -- SPM Characterization of Catalysts -- SPM Characterization of Biomaterials -- SPM Characterization of Organic and Polymeric Materials -- Theories of SPM -- When Will SPM Realize Our Dreams? The Roadmap of SPM.
Keywords: Nanotechnology; Condensed matter; Engineering; Materials—Surfaces.; Thin films; Nanotechnology; Condensed Matter Physics; Engineering, general; Surfaces and Interfaces, Thin Films